Claim Audit by BPKP (Financial and Development Supervisory Agency) on Construction Contracts in BUMN - Efendy, Prasetyo; Sami’an, Sami’an; Hardjomuljadi, Sarwono (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Construction service work is the most complex work compared to other industries. It is not surprising that in the implementation of construction service work, things arise that deviate from the initial planning, resulting in claims by the Provider of Goods/Services to the User of Goods/Services. In construction service work owned by BUMN (State-Owned Enterprises), several construction claims that have occurred that have been previously reviewed by the Provider of Goods/Services, are continued for the claim audit process by BPKP (Financial and Development Supervisory Agency), especially for claims related to additional costs that are quite large in value. Of course, this requires a mutual agreement between the User of Goods/Services and the Provider of Goods/Services to jointly submit a claim audit application to BPKP. This claim audit application to BPKP is carried out to ensure the amount of the claim submitted by the Provider of Goods/Services, where BPKP is seen as a competent and experienced body for claim audits. Problems will arise if: The Provider of Goods/Services does not agree to the claim audit process to BPKP because it is not stated in the construction contract or the Provider of Goods/Services does not agree with the results of the claim audit conducted by BPKP. In the event that the claim is not fulfilled or resolved, it means that a dispute has occurred between the contracting parties. This dispute must be resolved through the legal channels chosen by the parties in the contract, either through Alternative Dispute Resolution (Consultation, Negotiation, Mediation, Conciliation, Expert Assessment), Arbitration, or through the Court. The dispute resolution process will take longer, so it is necessary to rethink whether this claim audit to BPKP can be a faster way to resolve construction contract claims.